(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In this article, the possibilities of preserving the existing industrial and technological potential and its export possibilities during the innovative development of the industry of the Tashkent region are analyzed. In addition, the need to pay attention to industrial activity in the region and the development of its statistical assessment system was emphasized. In the conclusion, the development trends of the production of innovative products in the region are listed one by one.